Visionary Leadership-Based Educational Management Model to Improve Vocational High School Teacher Performance - Amiruddin Amiruddin; Afif Alfiyanto (JUMPA : Jurnal Manajemen Pendidikan, 2026)
This study aims to develop and validate an educational management model based on visionary school leadership to enhance teacher performance in public vocational high schools in Langkat Regency. Employing a Research and Development approach with a modified Borg & Gall framework, the research progressed through preliminary assessment, model design, product development, and three sequential trial phases across eight schools. Data were collected using validated performance questionnaires and leadership perception scales, analyzed through paired sample t-tests. Results demonstrated significant improvements in teacher performance, with mean scores rising from 72.8 to 86.2 in the wide-scale trial (p < 0.001). Teachers’ perceptions of principals also shifted markedly toward visionary, participatory, and inspirational leadership. The finalized model integrates reflective supervision, principal-led coaching, collaborative teacher forums, and strategic vision reinforcement. These findings confirm that embedding visionary leadership into structured management practices effectively transforms administrative routines into sustainable professional development pathways. The model offers a contextual, empirically validated framework for regional education policymakers and school administrators seeking to improve teacher quality and institutional effectiveness in vocational education. The findings imply that educational management should institutionalize visionary leadership, reflective supervision, collaborative coaching, and continuous performance evaluation to strengthen teacher effectiveness and school improvement.